PENGARUH PENGGUNAAN ARTIFICIAL INTELLIGENCE TERHADAP PENGAMBILAN KEPUTUSAN BISNIS PADA UMKM - Hilda Yuliastuti; Fitri Melawati; Iwadiah Iwadiah; Elisa Khairani; Rahma Diana (POLITEKNIK LP3I JAKARTA, 2026)
The development of digital technology has driven the emergence of various innovations capable of supporting business activities, one of which is Artificial Intelligence (AI). AI technology enables business actors to process data quickly, produce accurate information, and provide recommendations that can be used as a basis for business decision-making. For Micro, Small, and Medium Enterprises (MSMEs), the use of AI is becoming increasingly important because it can help overcome resource limitations, improve operational efficiency, and strengthen competitiveness amidst increasingly dynamic business competition. This study aims to analyze the effect of the use of Artificial Intelligence on business decision-making in MSMEs. This study uses a quantitative approach with a survey method. Data were obtained by distributing questionnaires to MSMEs that have utilized digital technology in their business activities. The sampling technique used purposive sampling with the criteria for respondents being MSME owners or managers who have used Artificial Intelligence-based applications or systems. Data analysis was conducted using descriptive statistics, validity tests, reliability tests, and simple linear regression analysis to examine the effect of AI use on business decision-making. The results show that the use of Artificial Intelligence has a positive and significant effect on business decision-making in MSMEs. The use of AI has been proven to increase the speed of access to data analysis information, the ability to predict market conditions, and the effectiveness of business strategy development. Furthermore, AI helps MSMEs understand consumer needs, identify business opportunities, and reduce the risk of errors in decision-making. AI's ability to provide real-time information also enables businesses to respond to changes in the business environment more quickly and accurately.